Trends, challenges, and priorities for shared decision making in mental health: The first umbrella review. (June 2023) - Chmielowska, Marta; Zisman-Ilani, Yaara; Saunders, Rob; Pilling, Stephen
Background: Shared decision making (SDM) is a health communication model promoting patient-centered care that has not been routinely utilized in mental health. Inconsistent definitions, models, measurement tools, and lack of sufficient evidence for the effectiveness of SDM interventions are potential contributors to the limited use of SDM in mental health. Aims: (1) Provide the first systematic analysis of global development trends and challenges of SDM research; (2) clarify the meaning, role, and measurement of SDM in mental health; (3) create a theoretical framework for key effective SDM components to guide future development and implementation of SDM interventions. Methods: A comprehensive search strategy was conducted in CINAHL, PubMed, Scopus, MEDLINE, EMBASE, Cochrane Library, Web of Science, Scopus, and PsycInfo. Included reviews focused on SDM interventions for prevention and/or treatment of mental illness in adults. A narrative synthesis was performed to capture the range of interventions, populations, measurement tools, comparisons, and outcomes. Results: 10 systematic reviews of SDM in mental health were included with 100 nested studies spanning from 2006 to 2020. All reviews focused on dyadic and psychopharmacological decision-making. Primary outcomes of SDM in mental health interventions include treatment satisfaction, medication adherence, symptom severity, quality of life, and hospital readmissions. Participant-related factors unique to SDM in mental health, such as stigma and mental capacity, were not reported. Conclusions: The current landscape of SDM in mental health is overwhelmingly disconnected from the needs and experiences of potential end-users; clients, clinicians, and family members. Most SDM interventions and tools were adapted from physical health and are mainly geared to psychopharmacological decision-making. The SDM in Mental Health Framework (SDM-MH), developed here, expands the scope of decisions to non-psychopharmacological discussions, diversifies the pool of SDM participants and settings, and offers potential primary target outcomes of SDM in mental health to reduce heterogeneity across studies.